New-Materialist Bricolage: Presenting an Ontological Position for Qualitative Internet-Based Research - Flynn, Susan; Caffrey, Louise; Byrne, Julie; Conlon, Catherine (My University, 2025)
The purpose of this paper is to make a novel contribution to new-materialist approaches, toward advancing existing ontological debates. We present a new-materialist bricolage method that was developed from an existing interpretive Community of Practice (CofP) known as the Pivot Project research consortium. This interpretative community was used to theorise the ontological implications of research in the covid-19 global pandemic. The specific focus was on digitalisation of five qualitative multidisciplinary research projects because of the impacts of an unexpected pandemic. We were able to formulate a bespoke new-materialist bricolage that successfully allowed us to overcome existing impasses of our multidisciplinary ontological differences, whilst enabling us to remain attentive to both abstract and material considerations. We conclude by reflecting on what new-materialist ontology can tell us about what internet-based qualitative research is, could be and perhaps should be, in an ever-changing world.
PUBLISHED
DOI: 10.1080/13645579.2024.2329430
Keywords: new-materialism, ontology, qualitative research, documentary analysis